Evolução do relevo no divisor hidrográfico entre as bacias dos rios Grande e Paraíba do Sul: um estudo na Serra da Mantiqueira (MG/RJ) - Éric Andrade Rezende (2013)
The present work aims to study the relief evolution of a drainage divide section between the Grande River inland basin, one of the formers of the Paraná River, and the Paraíba do Sul River basin, locally represented by the headwaters of the Preto River. This drainage divide is contained in one of the higher portions of Mantiqueira Range and coincides with NNW flank of the Continental Rift of Southeastern Brazil. For this study nine sub-basins were selected in the extreme south of Minas Gerais, between the municipalities of Itamonte and Bocaina de Minas. These catchments had their denudational rates estimated by measuring the production of cosmogenic nuclide 10Be in fluvial sediments. The results show that the average denudation rate of the sub-basins of the Paraiba do Sul River, facing the graben (17,39 m/Ma), is greater than that of sub-basins of the Grande and Aiuruoca rivers, directed to continental interior (12,24 m/Ma). Therefore, these results confirm the occurrence of more intense erosive processes in watersheds facing the rift interior, as proposed in evolution models of escarpments located in mature passive margins. Among the control factors of the denudation rates, stands out a good correlation between rates and two morphometric parameters: relief amplitude and average slope of the catchments. The lithological influence is even more important, especially for the Granite Maromba, that is the more resistant lithological unit in the catchments sampled. A variety of evidence indicates that drainage rearrangements had fundamental importance in the neocenozoic evolution of drainage dividers studied. The probable capture of the upper Rio Preto, previously directed to the continental interior, was responsible for a considerable portion of the drainage divide retreat from the Resende Basin fault border. In combination with other geochronological data, the results also indicate the character predominantly episodic of the denudation at different time scales. The low denudation rates measured suggest relative tectonic stability in Upper Quaternary. Thus, the last tectonic event responsible for the rejuvenation of the relief area should be significantly older than the apparent age of the samples.